Relação da morfologia facial e o nível de sonolência em pacientes com a síndrome da apneia obstrutiva do sono - MOURA, Rafaela Farias de (2019)
INTRODUCTION: Obstructive sleep apnea syndrome (OSAS) is a chronic respiratory disorder characterized by obstruction of the upper airway during sleep. Excessive drowsiness, wakefulness and psychological changes such as stress and depression are the main symptoms of the syndrome. The objective of this study was to evaluate the relationship between facial morphology and the level of sleepiness in patients diagnosed with OSAS at a dental institute in Belém. METHODS: A convenience sample of patients with OSAS who sought the dental institute Dr. Fernão Flexa Ribeiro. Photographs of the documentation were used to perform the morphological analysis, where the patients were classified in relation to the facial biotype as: mesocephalic, brachycephalic and dolicocephalic. In relation to the facial profile as: straight, concave and convex and as for the hard palate were classified as: normal and ogival. The drowsiness scale was classified as follows: Less than 8 = normal drowsiness, 8-10 = mild drowsiness, 11-15 = moderate drowsiness, 16-20 = severe drowsiness, and 21-24 = excessive drowsiness. RESULTS: Of the charts analyzed, (50%) were women with mean age of 58 years and BMI of 28.4. (35.7%) of the men and (50%) of the women were classified as brachycephalic. As for the sleep scale, women had a higher percentage of moderate drowsiness, approximately 36%, in relation to men. When applied the Chi-Square test, Spearman correlation index and multiple linear regression analysis, the results obtained were not statistically significant (p> 0.05) for all variables. CONCLUSION: Data from this study were not able to confirm the relationship of facial morphology to the Epworth sleep scale. However, the analysis of facial morphology and drowsiness scale can be used to aid in the diagnosis of OSAS.